Good Bye, Coal - Tomczok, Marta; Grząślewicz, Tomasz (No Limits, 2023)
The fossil fuel extraction era in the Upper Silesia and Zagłębie region is coming to an end before our very eyes. However, coal is here to stay, as evidenced by heavy metal laden heaps and land subsidence. Research shows how large a role culture can play in taming decarbonisation. The researchers prove that we are in need of good transformation narratives, which could introduce us to the transition process from coal fueled electricity to nuclear energy.